A national hero or a Wily Politician? Students' ideas about the origins of the nation in Sweden. Issue 4 (4th July 2017) - Samuelsson, Johan; Wendell, Joakim
ABSTRACT: The topic of this article is how primary school students express ideas about the 'origins of the nation'. The study is based on texts written by Swedish students aged 12–13 about a historical event well embedded in Swedish national mythology, the rise to power of Swedish 'founding father' Gustav Vasa. The analysis is inspired by James V. Wertsch's concept of schematic narrative templates. The main finding of the study is that the students mainly structure their answers along one of two different narrative templates; either a kind of historical master narrative with strong foundations in traditional Swedish history culture, or a more generic story about the founding father as a ruthless or corrupt politician, which is arguably influenced by presentism.